2019
DOI: 10.1101/788695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanisms of activation and desensitization of full-length glycine receptor in membranes

Abstract: Glycinergic synapses play a central role in motor control and pain processing in the central nervous system. Glycine receptors (GlyR) are key players in mediating fast inhibitory neurotransmission at these synapses. While previous high-resolution structural studies have provided insights into the molecular architecture of GlyR, several mechanistic questions pertaining to channel function are still unknown. Here, we present Cryo-EM structures of the full-length GlyR protein reconstituted into lipid nanodiscs th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 82 publications
2
4
1
Order By: Relevance
“…In fact, the very recent cryo-EM structures of GlyR-a1 in a native lipid environment indicate that these leucines undergo a more pronounced rotation (away from the lumen) in the desensitized rather than the active state. However, this conclusion appears to be inconsistent with the very recent cryo-EM analysis of Kumar et al (2019).…”
Section: Resultscontrasting
confidence: 58%
“…In fact, the very recent cryo-EM structures of GlyR-a1 in a native lipid environment indicate that these leucines undergo a more pronounced rotation (away from the lumen) in the desensitized rather than the active state. However, this conclusion appears to be inconsistent with the very recent cryo-EM analysis of Kumar et al (2019).…”
Section: Resultscontrasting
confidence: 58%
“…Thus, the entry of GABAARs into the desensitized state could favour the dissociation of bound PIP2, in the process presenting the inositol head group for binding to the C2-domain of certain isoforms of PKC. Consistent with this, recent structural work on the glycine receptor, and on the prokaryotic channel ELIC, has shown that the straightening of the M4 helix in a desensitized conformation disrupts this lipid binding site 69,70 . Furthermore, simulations of the analogous phosphatidylserine binding site on the glycine receptor have also shown that lipid binding is favoured in the inactive conformation relative to the active one 71 .…”
Section: Discussionmentioning
confidence: 53%
“…In fact, the very recent cryo-EM structures of GlyR- α 1 in native lipid environments indicate that these leucines undergo a more pronounced rotation (away from the lumen) in the desensitized state rather than the active state. But, this conclusion is not supported by the very recent cryo-EM analysis of Kumar et al (Kumar et al, 2019).…”
Section: Figurementioning
confidence: 79%